The contemporary fatwa - Boubah, Abdi Salem Tayeb (Arab Journal for Sciences and Research Publishing, 2018)
This research tries to contribute to the enlightenment of the students of science, and to alert scholars in Fatwa to the truth of the contemporary fatwa, its importance and the need for its devotion to God. The Mufti must be observed in our time; circumstances, countries people, and understand the reality of it all.And then to refer to some of the qualities necessary in the Mufti, such as kindness for who asks questions and saying what is not surrounded by note: I do not know.
Keywords: Fatwa; Contemporary; Jurisprudence of Reality; Half of Knowledge; Don't Know